White fluorescence of polyaromatics derived from methanol conversion in Ca2+-exchanged small-pore zeolites. (28th April 2021) - Park, Hongjun; An, Jae Hwan; Bang, Jisuk; Ahn, Doo-Sik; Ko, Seung Hyeon; Terasaki, Osamu; Youn, Wongu; Choi, Insung S.; Ryoo, Ryong
Abstract : Methanol was converted to white-light fluorescent polyaromatics by the catalytic effect of Ca 2+ in ion-exchanged zeolite nanocages. Abstract : Coronene and its derivatives were synthesized using methanol inside Ca 2+ ion-exchanged small-pore zeolites with an 8-membered ring window, such as LTA and RHO zeolites. The polyaromatic hydrocarbon product exhibited white fluorescence under UV light excitation, as characterized by UV-Vis absorption and fluorescence spectra, and fluorescence microscopy images. The formation of coronene and even larger polyaromatics from methanol could be attributed to the fact that Ca 2+ ions, unlike the hydroxyl protons of acidic zeolite frameworks, effectively attract the π-electron clouds of benzene rings of small polycyclic intermediates with no disruption of the aromaticity, which leads to the rapid growth of the aromatic ring system. The molecular dimensions of the resultant polyaromatic product were determined by the confined α-cages of the LTA and RHO zeolites. This phenomenon could be extended to CHA zeolite with smaller pore sizes, restricting the molecular growth more severely than in the cases of LTA and RHO zeolites.